A high-flux isopore micro-fabricated membrane for effective concentration and recovering of waterborne pathogens - Warkiani, Majid Ebrahimi (2013)
A high-flux metallic micro/nano-filtration membrane has been fabricated and validated for isolation of waterborne pathogens from drinking water. Obtained membrane with smooth surface and perfectly ordered pores was achieved by a high yield and cost effective multilevel lithography and electroplating technique. The micro-fabricated membrane was also strengthened with an integrated back-support, which can withstand a high pressure during filtration. The results of microfiltration tests with model particles revealed the superior performance of the micro-fabricated filter than current commercial filters in sample throughput, recovery ratio, and reusability. This study highlighted the potential application of micro-fabricated filer in rapid filtration and recovery of C. parvum oocysts for downstream analysis.